(untitled) (Journal of Surgical Sciences, 2019)
Coronary artery bypass graft (CABG) surgery is one of the treatment modalities of coronary artery disease (CAD) patients. There are multiple selection criteria for CABG and multiple procedures like conventional CABG, on pump beating heart CABG and off pump beating heart CABG (OPCAB). This study was intended to compare between conventional CABG and on pump beating heart CABG. Total 60 patients were selected for the study, of which 30 patients had undergone conventional CABG and 30 had undergone on pump beating heart CABG. Different preoperative and postoperative variables shows clear and significant superiority of on pump beating heart CABG. So it may be an alternative surgical procedure where OPCAB is not feasible in poor left ventricular (LV) .function. Journal of Surgical Sciences (2014) Vol. 18 (1) : 20-27